Identifying risk factors for in-stent restenosis in symptomatic intracranial atherosclerotic stenosis: a systematic review and meta-analysis - Wang, Ning; Lu, Yuning; Feng, Lei; Lin, Dongdong; Gao, Yuhai; Wu, Jiong; Wang, Ming; Wan, Shu (Frontiers in Neurology, 2023)
BACKGROUND: In-stent restenosis (ISR) is an undesirable and remarkable event for the treatment of intracranial atherosclerotic stenosis (ICAS) with percutaneous transluminal angioplasty and stenting (PTAS). The incidence and contributing factors have not been fully defined. This study was performed to evaluate factors associated with ISR after PTAS. DATA SOURCE: We identified studies on ISR after PTAS from an electronic search of articles in PubMed, Ovid MEDLINE and the Cochrane Central Database (dated up to Jul 2022).RESULTS: Nineteen studies altogether, including 452 cases of ISR after 2047 PTAS, were included in the meta-analysis. The pooled incidence rate of in-stent restenosis was 22.08%. ISR was more likely to occur in patients with coronary artery disease (OR =1.686; 95% CI: 1.242-2.288; p=0.0008), dissection (OR =6.293; 95% CI: 3.883-10.197; p<0.0001), and higher residual stenosis (WMD =3.227; 95% CI: 0.142-6.311; p=0.0404). Patients treated with wingspan stents had a significantly higher ISR rate than those treated with Enterprise stents (29.78% versus 14.83%, respectively; p <0.0001).The present study provides the current estimates of the robust effects of some risk factors for in-stent restenosis for intracranial atherosclerotic stenosis. The enterprise stent had advantages compared with the wingspan stent for ISR. The significant risk factors for ISR were coronary artery disease, dissection and high residual stenosis. Local anaesthesia was a suspected factor associated with ISR.